Correlates of sexual inactivity and met need for contraceptives among young women in Ghana - D. Yaw Atiglo; Adriana A. E. Biney (BMC, 2018)
Abstract Background Young women in sub-Saharan Africa continue to experience unintended pregnancies despite effective contraceptive methods being more readily available than ever. This study sought to determine the correlates of met need for contraceptives and sexual inactivity among young women in Ghana who want to postpone childbearing. We examine this among all women and then separately by marital status. Methods Using data from 1532 females aged 15-24 years from the 2014 Ghana Demographic and Health Survey, we conducted descriptive and multinomial logistic regression analyses to assess sociodemographic, economic and obstetric determinants of the type of family planning method (current abstinence, modern contraceptive method) used by married and unmarried young women. Results A higher proportion (~ 44%) of the respondents was currently abstinent compared to those with met need (~ 25%). Abstinence was higher among single young women while unmet and met need were higher among the married. Having at least senior high school education was significantly associated with the likelihood of current abstinence (especially among single women) and with met need. Being in the middle and rich categories, on the other hand, was associated with lower likelihood of current abstinence and a met need. Compared with multiparous women, those with one or no surviving child had a lower likelihood of being abstinent and having a met need. Other correlates of both current abstinence and met need are region of residence and ethnicity, while previous pregnancy termination and age were associated with abstinence and contraceptive use, respectively. Conclusions Unmet need is high among young women but abstinence is an option they are using. As reproductive health programmes target the at-risk groups, the secondary and higher educational levels must be attained by most women as this is associated with use of abstinence and met need.